2022
DOI: 10.3390/app12020543
|View full text |Cite
|
Sign up to set email alerts
|

How Do German Manufacturers React to the Increasing Societal Pressure for Decarbonisation?

Abstract: From the perspective of manufacturing companies, the political, media and economic discourse on decarbonisation in the recent years manifests itself as an increasing social expectation of action. In Germany, in particular, this discourse is also being driven forward by powerful companies, respectively sectors, most notably the automotive industry. Against this background, the present paper examines how German manufacturing companies react to rising societal pressure and emerging policies. It examines which mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Table 1 provides an overview of the sample by company size (as defined by the European Commission [32]). As explained by Buettner et al [33] (pp. 3-4), we aim for an approximately even distribution across company sizes for EEI's samples instead of following the actual size distribution of manufacturing companies in Germany [28].…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…Table 1 provides an overview of the sample by company size (as defined by the European Commission [32]). As explained by Buettner et al [33] (pp. 3-4), we aim for an approximately even distribution across company sizes for EEI's samples instead of following the actual size distribution of manufacturing companies in Germany [28].…”
Section: Methodsmentioning
confidence: 79%
“…Automotive industries and mechanical engineering are two of the eleven sectors of high importance for German industry. When taking a sectoral viewpoint in this paper, only sectors with at least 20 companies providing answers to the respective questions are considered [33].…”
Section: Methodsmentioning
confidence: 99%
“…The present article addresses this gap by illustrating what seven foundational questions matter and need answering to provide practical guidance on how to shape an effective and tailored decarbonisation strategy. Derived from professional practice and applying a mix-methods approach building on data gathered via the Energy Efficiency Index of German Industry (EEI) [29], the work addresses underlying motivations and spans across (socio-)economic, technical, regulatory, strategic, corporate culture and environmental factors and further underlines the necessity of a mutual understanding, clarity and communication of definitions and targets.…”
Section: The Issue: Enabling Corporate Stakeholders To Decarbonise Ef...mentioning
confidence: 99%
“…By when do companies plan to reach net carbon neutrality? [29][30] Taking the likely impact of the COVID-pandemic into consideration and addressing the apparently important milestone year 2025, the first iteration of EEI in 2020 found that the 611 participating companies on average, and based on 2019 figures, aim at reducing their GHG emissions by 22.09 % by then [31]. Asking for their 2030 ambitions at the time when the enhanced target of the European Commission for 2030 was being discussed (autumn 2020), 415 companies participating in the 2 nd data collection of EEI in 2020 expressed to aim for a 26.43 % GHG reduction (based on 2019) [32].…”
Section: Level Of Ambitionmentioning
confidence: 99%
See 1 more Smart Citation